EFFECT OF PROPAGATION MEDIA AND BLACK POLYBAGS ON GROWTH AND SURVIVAL OF BUDDED KINNOW PLANTS - K. MOHD ILYAS, AKASH SHARMA, SOHNIKA RANI, V. K. WALI PARSHANT BAKSHI (The Bioscan, 2015)
The present study showed that the plants planted in black poly bag with holes of size 22x10x8 cm filled with propagation media soil: sand: vermicompost in the ratio of 1:1:1 recorded highest out planting performance (survival percentage) 93.33per cent with maximum leaf area (15.21 cm2), number of primary roots (12.00) and secondary roots (99.67) as compared to other treatments. Similar treatment also showed maximum soil nitrogen (299 kg ha-1), phosphorous (20.78 kg ha-1), potassium (177.67 kg ha-1), calcium (7.18 meq/100g) and magnesium (3.45 meq/100g) respectivelyafter six months of budded kinnow plants planted in black polybags.